Synthesis and molecular docking studies of new fragrant campholenal derived succinate diesters - Cat, Yesim; Eran, Belkiz Bilgin; Sagirli, Akin; Acar, Havva; Tasdemir, Harun; Kavas, Ozge; Yazici, Onur Can (TAYLOR & FRANCIS INC, 2026)
Succinate diesters are a versatile class of compounds with diverse applications owing to their unique chemical properties. This study reports the synthesis of novel campholenal-derived succinate diesters, exploiting the structural diversity of campholenal, an important raw material in fragrance chemistry. Monoester succinates were first prepared from low-molecular-weight alcohols and subsequently esterified with campholenol and its alpha-methyl- and alpha-dimethyl-substituted derivatives to afford a series of diesters. All intermediates and final products were structurally characterized by IR, NMR, and TOF-LCMS analyses. Olfactory evaluation by an expert panel revealed that propyl-substituted derivatives exhibited enhanced odor longevity, while methyl and dimethyl substitutions on the campholenol moiety significantly influenced odor characteristics. To rationalize these observations at the molecular level, docking studies of compounds 9a-i were performed against the human olfactory receptor OR51E2. The results supported the experimental findings by indicating favorable binding affinities and interaction patterns for compounds associated with increased odor durability.
Keywords: Succinate diester; odor; campholenal; succinic anhydride; molecular docking; ANALOGS; Chemistry